Development of product sharing and search system (Part II Android) - Chung, Qiwen (2014)
The purpose of the project is to develop a product sharing and search system to leverage on the still quite untapped mobile commerce market in Singapore. The mobile commerce market is growing at an exponential rate, generating large number of transactions in Singapore. Developing a mobile commerce android application is ideal in Singapore where smartphones penetration is high when compared to other nearby countries in the Asia Pacific region. As most of the features were completed by previous team members, this project mainly focuses on the search feature as this is a product sharing and search system. The user interfaces of the android features were designed similarly to Instagram and Pinterest UI as their UI provide users with ease of use, with no steep learning curve at all. Without a steep learning curve to learn to learn how to use the UI, this means greatly improve user experience. The report also discusses the development process, the software used, and the requirements gathering of the project which is actually covered under user interface design as the functions in this project are based on Instagram’s and Carousell’s existing functions. This means DealsInterest application features will be 80% similar to those of Instagram and Carousell. Problems encountered by the author during the implementation process will also be discussed and future enhancements will be discussed in the recommendations section. And lastly, the report summarises what have been done in the conclusion section.